Thermal and thermodynamic stability of nanomaterials : special topic volume with invited peer reviewed papers only - Parida, Suresh Chandra (Materials science forum, 2010)
The study of nanomaterials is an active area of 21st-century research in physics, chemistry and materials engineering as well as biomedical engineering. Nanomaterials which are defined as substances that are in the form of spherical dot, rod, thin plate or voids of any irregular shape, but smaller than 100nm, find wide application in materials science and technology due to their very distinctive properties as compared with their bulk counterpart. This special volume is focused on two fundamental issues related to the stability of nanomaterials. Thermal stability is a very important issue in controlling the size during synthesis, as well as in high-temperature environments. The thermodynamic stability of nanomaterials²⁶ is very important in understanding the underlying principle behind their formation from atomic or molecular constituents via the bottom-up approach or via the disintegration of larger particles via the top-down approach.²⁶ Large variations in thermo-physical properties such as melting-point, enthalpy of formation, etc., have been observed in nanomaterials; unlike their bulk counterparts. The underlying principles behind these anomalous properties are addressed by some of the articles in this volume. Overall, the present articles will provide many important guidelines for researchers working on fundamental and technical issues in the field of nanomaterials.